2004
DOI: 10.1007/s10286-004-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

Permanent cardiac pacing as primary therapy for neurocardiogenic (reflex) syncope

Abstract: Recurrent reflex (or neurocardiogenic) syncope is a common clinical problem. Pacemaker therapy has been advocated as a potential therapy in severe or drug refractory cases of reflex syncope, while others have suggested that it may provide a benefit if employed as a primary therapeutic modality. The following paper reviews the concepts behind pacemaker therapy for reflex syncope and the results of various clinical trials that have evaluated its potential utility as a primary therapeutic modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…25 Rate drop algorithm is more complicated as it introduces rapid dual chamber pacing if the device detects a rapid reduction in heart rate. 8 Ammirati et al 27 suggested that dual chamber pacing with a rate-drop algorithm was more effective than dual chamber pacing with hysteresis algorithm. However, a recent study showed that the conventional pacemaker algorithm does not significantly reduce syncopal episodes 7 and the rate-only sensing algorithm of conventional pacemaker results in sensing the VVS process when it is well underway and provides the behind time pacing.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…25 Rate drop algorithm is more complicated as it introduces rapid dual chamber pacing if the device detects a rapid reduction in heart rate. 8 Ammirati et al 27 suggested that dual chamber pacing with a rate-drop algorithm was more effective than dual chamber pacing with hysteresis algorithm. However, a recent study showed that the conventional pacemaker algorithm does not significantly reduce syncopal episodes 7 and the rate-only sensing algorithm of conventional pacemaker results in sensing the VVS process when it is well underway and provides the behind time pacing.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Hysteresis algorithm allows the pacing rate to surpass the lower limit of heart rate for a programmable period of time . Rate drop algorithm is more complicated as it introduces rapid dual chamber pacing if the device detects a rapid reduction in heart rate . Ammirati et al suggested that dual chamber pacing with a rate‐drop algorithm was more effective than dual chamber pacing with hysteresis algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with neurocardiogenic syncope, an increase in cardiac contractility may precede fall in blood pressure and heart rate, leading to syncope. 11,12 Conventional pacing systems can only detect changes in heart rate; thus it senses the occurrence of syncope only TA B L E 1 Classification of VVS based on response to HUTT…”
Section: Basic Concepts Behind Cls Pacingmentioning
confidence: 99%